The October 1979 Change in the U.S. Monetary Regime: Its Impact on the Forecastability of Canadian Interest Rates - PESANDO, JAMES E.; PLOURDE, ANDRÉ (Journal of Finance, 1988)
ABSTRACT Subsequent to the October 1979 shift in monetary policy in the United States, interest rates in North America not only reached unprecedented levels but also exhibited unprecedented volatility. Using Canadian data, the authors show that anticipated quarterly changes in long‐term rates associated with the rational‐expectations model have remained small during this post‐shift period. The authors examine three sets of recorded forecasts of long‐term interest rates in Canada and note their failure to improve upon the no‐change prediction. The “perverse” relationship between the slope of the yield curve and the subsequent movement in long‐term rates exists in the Canadian data but is of only modest value in a forecasting context. The excess returns on long‐term bonds implicit in the recorded forecasts of the level of interest rates vary sharply, yet there is little evidence that forecasters have identified a predictable component of time‐varying term premia.